A case study of the merchandising flow of "George Machado," a product line of Jourdan et Cie. - Romano, Raymundo S.
The study aimed to present an over-all view of the merchandising flow of Jourdan et Cie. It also concentrated on the merchandising schedule of George Machado, one of the company's product lines. To fulfill the objectives of the study, the researcher rendered a significant amount of time at the merchandising department of the company from the first week of November 1989 until the last week of January 1990. Collection of primary data for this research was conducted through personal interviews with the merchandisers, along with actual observations of the varied activities within the merchandising department of Jourdan et Cie. Said company's merchandising calendar, documents and other written materials provided the secondary sources. The study revealed that there was a two-week delay in the prototype sample development of the ten (10) styles of the George Machado line. The delay was due to the following reasons: non-conformance to specifications, last minute cancellation/revision of designs, inability of merchandisers to inspect the quality of fabrics, accessories and trims, and shortage of accessories needed. However, the delays encountered at the merchandising department of the company during the months prior to the March 1990 deadline were not directly responsible for the late arrival of goods to the designed outlets. The reason for the late delivery of merchandise to the designed outlets was beyond the control of the merchandising department. The main reason for the late arrival of the merchandise to the designated outlets was the company's inability to pay its subcontractors on time.